Concepts in soft-tissue reconstruction of the contracted hand and upper extremity after burn injury - McNamara, Colin T.; Iorio, Matthew L.; Greyson, Mark (Frontiers in Surgery, 2023)
Burns and their subsequent contracture result in devastating functional and aesthetic consequences which disproportionally affect the upper extremity. By focusing on reconstruction with analogous tissue and utilizing the reconstructive elevator, function can be restored concomitantly with form and aesthetic appearance. General concepts for soft-tissue reconstruction after burn contracture are presented for different sub-units and joints.